2004
DOI: 10.1051/fruits:2004035
|View full text |Cite
|
Sign up to set email alerts
|

Influence of rootstock on the productive behaviour of ‘Orange Red’ apricot under Mediterranean conditions

Abstract: --Introduction. 'Orange Red' is an apricot cultivar released in the United States and characterised by large fruit of very good quality for both the fresh market and processing. For this reason, this cultivar is greatly appreciated in Europe, especially in France. However, its production is erratic under Mediterranean climate conditions. Materials and methods. The influence of two rootstocks ('Manicot' apricot and 'GF31' Myrobolan plum) on the productive behaviour of 'Orange Red' was studied under Mediterranea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…In this context, Egea et al (2004) reported that interaction between apricot cultivars and rootstocks is presented as an interesting strategy for cultivar adaptation to different soil and climatic areas.…”
Section: Evaluation Of Tree Growth Yield Characteristics and Fruit Wmentioning
confidence: 99%
See 3 more Smart Citations
“…In this context, Egea et al (2004) reported that interaction between apricot cultivars and rootstocks is presented as an interesting strategy for cultivar adaptation to different soil and climatic areas.…”
Section: Evaluation Of Tree Growth Yield Characteristics and Fruit Wmentioning
confidence: 99%
“…On the other hand, the lowest CY and YE were observed in 'Biljana'. Ondradu & Scalas (1999) and Egea et al (2004) stated that some apricot cultivars grafted on Myrobalan gave the highest yield than other rootstocks. In contrast, some authors from different countries reported that cultivars on Myrobalan produced smaller yield then on apricot seedlings and/or on other rootstock for apricot (Loreti et al 2000;Son & Küden 2003).…”
Section: Evaluation Of Tree Growth Yield Characteristics and Fruit Wmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, fruit weight is affected by crop load, and there is a correspondence between low yield and large fruit weight (Egea et al, 2004) and vice versa. However, in our study, no significant correlation was found between fruit weight and yield.…”
Section: Fruit Qualitymentioning
confidence: 99%